Comparison of results of Bakri balloon tamponade and caesarean hysterectomy in management of placenta accreta and increta: a retrospective study - Pala, Sehmus; Atilgan, Remzi; Baspinar, Melike; Kavak, Ebru Celik; Yavuzkir, Seyda; Akyol, Alparslan; Kavak, Burcin (Taylor & Francis Inc, 2018)
The aim of this study was to compare the postoperative results of the patients who were treated with Bakri balloon tamponade or hysterectomy for placenta accreta and increta. Patients who were diagnosed with placenta accreta or increta preoperatively and intraoperatively and treated with Bakri balloon tamponade (Group 1) or caesarean hysterectomy (Group 2) were compared in regards to the postoperative results. Among the 36 patients diagnosed with placenta accreta or increta, 19 patients were treated with Bakri balloon tamponade while 17 cases were treated with hysterectomy. Intraoperative blood loss amount was 1794725ml in G1, which was lower than that in G2 (2694893ml). Blood transfusion amount was 2.72.6 units in G1, lower than that in G2 (5.7 +/- 2.4 units), too. Operation time was 64.5 +/- 29min and 140 +/- 51min in G1 and G2, respectively, showing significant differences between two groups. The success rate of Bakri balloon was determined as 84.21%. In conclusion, cases with placenta accreta/increta, with predicted placental detachment who are willing to preserve fertility, application of uterine balloon tamponade devices before the hysterectomy is encouraging with its advantages compared with the hysterectomy.Impact statementWhat is already known on this subject: Invasive placental anomalies are the most common indication of postpartum hysterectomy. Recently, uterine balloon tamponade was also included in the treatment modalities of postpartum haemorrhage.This study aimed to compare the postoperative results of UBT or hysterectomy for patients with placenta accreta and increta.What the results of this study add: In this study, the total amount of blood loss was higher in the caesarean hysterectomy group when compared with the Bakri balloon tamponade group. The mean transfusion requirement, mean operation time and hospitalisation period was significantly longer in the caesarean hysterectomy group. The success rate of the Bakri balloon was determined as 84.21%. Two patients who were treated with balloon application had a successful pregnancy and delivery later. Maternal mortality was reported in neither balloon nor hysterectomy groups.What the implications are of these findings for clinical practice and/or further research: In conclusion, patients diagnosed with placenta accreta/increta with ultrasound should be taken into the operation in elective conditions, if possible, on lithotomy position. In cases with predicted placental detachment that are willing to preserve fertility, application of uterine balloon tamponade devices before the hysterectomy has advantages compared with the hysterectomy.
Keywords: Placenta accreta; Bakri balloon; postpartum hysterectomy